An ultrasonics based system for the extraction of range and bearing data for multiple targets - Webb, Philip Francis (1994)
With the increasing use of automatically guided vehicles and a requirement for greater flexibility from fixed robots there is a need for a system which can locate and map the position of objects within a defined workspace in real time. The purpose of this research is to design and evaluate a system which will provide a possible solution to this problem using ultrasonics and to investigate the applicability of different signal processing strategies to the enhancement of such data.